Schwarz Method for Financial Engineering (Journal of Computational Mathematics, 2021)
Schwarz method is put forward to solve second order backward stochastic differentialequations (2BSDEs) in this work. We will analyze uniqueness, convergence, stability andoptimality of the proposed method. Moreover, several simulation results are presented todemonstrate the effectiveness; several applications of the 2BSDEs are investigated. It isconcluded from these results that the proposed the method is powerful to calculate the2BSDEs listing from the financial engineering.
Keywords: 2BSDE; Schwarz method; Domain decomposition; Viscosity solution; Stochastic volatility models.